THE RELEVANCE OF PREVENTION IN CHRONIC BRONCHITIS - Dilafruz Ravshanbekovna Abzalova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Bronchitis is a pathological condition in which inflammation of the bronchi develops. Respiratory diseases are chronic non-infectious diseases and are one of the most socially and economically significant groups of diseases today. International studies have shown that over the past 10 years the number of patients with chronic respiratory diseases has doubled. In the chronic form, the main cause of development is recognized as smoking. Smokers are diagnosed with the disease 2-5 times more often than non-smokers. Chronic bronchitis differs from acute in its etiology, pathophysiology and treatment methods.